Panni tartarici and other oriental textiles in the Castilian ecclesiastical context (1270-1385) - Barrigón , María (De Medio Aevo, 2025)
This article analyzes, for the first time, the existence of panni tartarici and other oriental fabrics in the Castilian Church between 1270 and 1385 through documentary sources, thus demonstrating the existence therein of luxury materials the same as those used in the rest of the Western kingdoms. Worth noting is not only the abundance of terms such as panni tartarici, suria, damasco, bucaran or tapete among others but also, on occasions, the numerous mentions of some of them in the inventories. These documentation enables us to identify several details about certain fabrics and antedate the appearance of some in Castile compared to what had hitherto been estimated.